Cystic fibrosis: An update for clinicians. Part 2: Hepatobiliary and pancreatic manifestations. Issue 12 (18th November 2014) - Ledder, Oren; Haller, Wolfram; Couper, Richard TL; Lewindon, Peter; Oliver, Mark
Abstract This paper, the second in the series, will build on the first and explore the importance of liver and pancreatic manifestations of cystic fibrosis (CF) and the effect on morbidity and mortality of this multifaceted genetic condition. It will also further develop the critical role of the gastroenterologist as part of the multidisciplinary group of clinicians and allied health staff in the effective management of patients with CF.